2008 IEEE Radio and Wireless Symposium 2008
DOI: 10.1109/rws.2008.4463550
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in integrating embedded RF within a SOC

Abstract: The challenges of integrating an embedded RF function within a system-on-chip (SOC) are outlined. An aggressive market need, combined with stringent technical difficulties, drives the need for an improved design methodology. Architecture innovations allow optimal building of RF within advanced CMOS. Antenna coexistence and substrate co-habitation have also to be addressed especially in multi-mode platforms. Only total deployment of design for excellence (DFx) procedures enables achieving production yield and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The technology is realized by two components, which are the mobile RFID tag as the transmitter and four units of low power data radio modules, (LPDRM) as the RFID readers. In [2,[11][12][13][14][15][16][17], RSSI is a parameter that has been used in predicting the location of a wireless device and estimating the distance traveled by a transmitted signal to reach the receiver. Instead of using complicated localization algorithm such as MUSIC algorithm [17], the mobility of the RFID tag and the 'pyramid' structure of the RFID readers' antenna which has four sections with leaned at 45 • angle for every single section enable the proposed system to perform the same function efficiently as an easier approach.…”
Section: Introductionmentioning
confidence: 99%
“…The technology is realized by two components, which are the mobile RFID tag as the transmitter and four units of low power data radio modules, (LPDRM) as the RFID readers. In [2,[11][12][13][14][15][16][17], RSSI is a parameter that has been used in predicting the location of a wireless device and estimating the distance traveled by a transmitted signal to reach the receiver. Instead of using complicated localization algorithm such as MUSIC algorithm [17], the mobility of the RFID tag and the 'pyramid' structure of the RFID readers' antenna which has four sections with leaned at 45 • angle for every single section enable the proposed system to perform the same function efficiently as an easier approach.…”
Section: Introductionmentioning
confidence: 99%
“…In [15,[17][18][19][20][21][22], received signal strength indicator (RSSI) is a parameter that has been used in predicting the location of wireless device in Wi-Fi positioning systems. To the authors' knowledge, none of these designs has demonstrated an adaptive Wi-Fi system using a combination of RFID technology with reconfigurable beam shape antenna controlled by PIC microcontroller.…”
Section: Introductionmentioning
confidence: 99%